Overall survival and histology‐specific subgroup analyses from a phase 3, randomized controlled study of trabectedin or dacarbazine in patients with advanced liposarcoma or leiomyosarcoma. Issue 15 (7th June 2019) - Patel, Shreyaskumar; von Mehren, Margaret; Reed, Damon R.; Kaiser, Pamela; Charlson, John; Ryan, Christopher W.; Rushing, Daniel; Livingston, Michael; Singh, Arun; Seth, Rahul; Forscher, Charles; D'Amato, Gina; et al.
Abstract : Background: We performed a randomized phase 3 study of trabectedin versus dacarbazine in previously‐treated patients with liposarcoma/leiomyosarcoma (LPS/LMS). Methods: Patients were randomized 2:1 to trabectedin (n = 384) or dacarbazine (n = 193) administered intravenously every 3 weeks. The primary objective was overall survival (OS). Secondary objectives were progression‐free survival, objective response rate, safety, and patient‐reported outcomes, all previously reported and demonstrating superior disease control with trabectedin. Results of the final OS analysis in preplanned subgroups of patients with LPS/LMS are presented. Results: At the time of the final OS analysis, 577 patients had been assigned randomly, including 423 (73%) with LMS and 154 (27%) with LPS. The median duration of treatment exposure was higher in the trabectedin arm compared with the dacarbazine arm (4 vs 2 cycles), as was the proportion of patients receiving an extended number of therapy courses (≥6 cycles: 42% vs 22%). This pattern was consistent across histological subgroups: the median number of treatment cycles (4 vs 2 for both subgroups) and proportion of patients with ≥6 treatment cycles (LMS, 43% vs 24%; LPS, 40% vs 16%). Despite improved disease control by trabectedin, no improvement in OS was observed; the final median OS for trabectedin versus dacarbazine was 13.7 versus 13.1 months ( P  = .49). Sensitivity analyses of OS suggest confounding by post‐study anticancer therapies, which were utilized in most patients in both treatment arms (71% vs 69%, respectively). Conclusion: The final OS results demonstrated comparable survival between LPS/LMS patients receiving trabectedin or dacarbazine, which is consistent with the interim analysis results. Both LPS and LMS demonstrated improved disease control with trabectedin. Abstract : A final analysis of overall survival demonstrates comparable results between patients with liposarcoma/leiomyosarcoma receiving trabectedin or dacarbazine, which is consistent with interim analysis results. Both liposarcoma and leiomyosarcoma show improved disease control with trabectedin.